Center-specific variation in outcomes for extremely premature, extremely low birth weight neonates - Kalyanam, Sai Manasa; Kuiper, Jordan R.; Iwashyna, Theodore J.; Knake, Lindsey A.; Lee, Esther G.; Wynn, James L.; Aziz, Khyzer B. (Frontiers in Pediatrics, 2025)
The survival rate of neonates born with extremely low birth weight (<1,000 g) and extremely preterm (<29 gestational age) has significantly improved with advances in neonatal care. Despite such advances, outcomes vary widely across neonatal intensive care units due to differences in care practices and patient population. In this study, we examined 1,627 extremely low birth weight and extremely preterm infants admitted to three NICUs across the United States between 2013 and 2023. We evaluated survival and severe intraventricular hemorrhage (SIVH) using statistical models that were adjusted for maternal and neonatal characteristics. Significant differences in outcomes were observed between the centers. These differences were associated with variations in care practices, including resuscitation decisions for the infants. Despite these differences, all centers achieved survival without SIVH for a substantial number of infants, annually. These findings emphasize the need for evidence-based practice-sharing and improvements to ensure better and more consistent care.